2022
DOI: 10.3390/diagnostics12061390
|View full text |Cite
|
Sign up to set email alerts
|

Predicting CT-Based Coronary Artery Disease Using Vascular Biomarkers Derived from Fundus Photographs with a Graph Convolutional Neural Network

Abstract: The study population contains 145 patients who were prospectively recruited for coronary CT angiography (CCTA) and fundoscopy. This study first examined the association between retinal vascular changes and the Coronary Artery Disease Reporting and Data System (CAD-RADS) as assessed on CCTA. Then, we developed a graph neural network (GNN) model for predicting the CAD-RADS as a proxy for coronary artery disease. The CCTA scans were stratified by CAD-RADS scores by expert readers, and the vascular biomarkers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The sensitivity, precision, F1-Score, and accuracy metrics were evaluated for each model. In contrast, existing models like NSCGCN [17], PNA-GCN [9], ResGNet-C [65], Efficient-B4-FPN [66], and GraphSAGE [67] demonstrate lower accuracy levels ranging from 63.83% to 98.04%. The highest accuracy was achieved by NSCGCN [17] at 98.04% and by PNA-GCN [9] at 97.79%, demonstrating the second-highest accuracy.…”
Section: Comparison Performance Of Proposed Models With Other Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…The sensitivity, precision, F1-Score, and accuracy metrics were evaluated for each model. In contrast, existing models like NSCGCN [17], PNA-GCN [9], ResGNet-C [65], Efficient-B4-FPN [66], and GraphSAGE [67] demonstrate lower accuracy levels ranging from 63.83% to 98.04%. The highest accuracy was achieved by NSCGCN [17] at 98.04% and by PNA-GCN [9] at 97.79%, demonstrating the second-highest accuracy.…”
Section: Comparison Performance Of Proposed Models With Other Literaturementioning
confidence: 90%
“…The highest accuracy was achieved by NSCGCN [17] at 98.04% and by PNA-GCN [9] at 97.79%, demonstrating the second-highest accuracy. GraphSAGE [67] achieved the lowest accuracy at 63.83% in the classification results. Notably, DeepChestGNN outperforms other models with exceptional metrics: sensitivity of 98.72%, precision of 98.71%, F1-Score of 98.71%, and an impressive accuracy of 99.74%.…”
Section: Comparison Performance Of Proposed Models With Other Literaturementioning
confidence: 97%
“…Traditionally, most existing algorithms simply measure success in terms of detection accuracy, where the CVD risk is calculated by conventional equations. For instance, [27, 28, 49, 50] report the outcomes of their algorithms in terms of AUC, regarding successful models as those that have an AUC > 0.70. Although this approach has its merits merely knowing that a model can predict CVD risk with an AUC > 0.70 is of limited value because simply achieving a high level of accuracy does not necessarily mean that the algorithm has learnt what was expected.…”
Section: Discussionmentioning
confidence: 99%
“…This is a combination of 3D CNNs AND LSTM. Fan Huang et al [145] focused on predicting coronary artery disease (CAD) from CT scans using vascular biomarkers derived from fundus photographs through a GNN. This method showed that specific retinal vascular biomarkers, such as arterial width and fractal dimensions, were significantly associated with adverse CAD-RADS scores.…”
Section: Graph Neural Networkmentioning
confidence: 99%